Ten-year outcome of chronic thromboembolic pulmonary hypertension patients in a tertiary center - (:unkn) unknown (TURKISH SOC CARDIOLOGY, 2019)
Objective: Chronic thromboembolic pulmonary hypertension (CTEPH) is one of the leading causes of pulmonary hypertension (PH). We aimed to investigate the outcome of CTEPH patients who were followed-up by a PH outpatient clinic. Methods: We screened the medical records of 29 PH patients who were followed-up by a PH outpatient clinic between 2009 and 2018. The patients' demographics and their clinical, echocardiographic, and hemodynamic characteristics were recorded. Results: Our study group consisted of 16 females (55.2%) and 13 males (44.8%). The mean age was 59.5 +/- 13.7 years and the median follow-up duration was 44 months (1-113 months). The mean initial 6-minute walking distance (6MWD) was 321.4 +/- 119.9 m. The initial median N-terminal pro brain natriuretic peptide (NT-proBNP) level was 2468 pg/mL (46.1-20.564 pg/mL). All patients were on oral anticoagulant therapy. Pulmonary endarterectomy (PEA) was performed in 17 of 29 patients (58.6%). Twelve patients (41.4%) were not operated upon due to distal disease, comorbidities, or their own preference. The operated patients were younger than the non-operated patients (55 years & 65 years, p=0.04). At the follow-up, the 6MWD in the operated patients increased (+76 m) and decreased in non-operated patients (-46 m). The survival rate at 10-year follow-up was 58.6% for the whole group. Twelve patients died during the follow-up period. While 7 of 12 not-operated patients died (58.3%), just 5 of 17 operated patients (4 perioperatively and 1 at follow-up) died (29%). Advanced-stage final functional capacity (FC) [New York Heart Association (NYHA) III-IV], inoperability, lower final 6MWD, higher final NT-proBNP, and reduced tricuspid annular plane systolic excursion (TAPSE) were associated with an increased mortality rate. Univariate Cox regression analysis showed that patients with NYHA I-II final FC showed a 166-fold decreased mortality rate. Conclusion: The long-term prognosis of operated patients is better than the outcome of not-operated patients. The strongest predictor associated with mortality was a worse final FC (NYHA III-IV).
Keywords: chronic thromboembolic pulmonary hypertension; endarterectomy; follow-up; mortality; TREATED PATIENTS; ENDARTERECTOMY; EXPERIENCE